2013
DOI: 10.1111/cod.12141
|View full text |Cite
|
Sign up to set email alerts
|

Nickel and cobalt release from jewellery and metal clothing items inKorea

Abstract: Our study shows that the prevalence of items that release nickel or cobalt among jewellery and metal clothing items is high in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…12 Nickel allergy is common worldwide, but cobalt allergy is uncommon in some countries. 12 Nickel allergy is common worldwide, but cobalt allergy is uncommon in some countries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Nickel allergy is common worldwide, but cobalt allergy is uncommon in some countries. 12 Nickel allergy is common worldwide, but cobalt allergy is uncommon in some countries.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative measurements using the EN 1811 reference method or x-ray fluorescence spectroscopy are expensive, time consuming, and potentially destructive to the test items. 12 Hamann et al, 3 using DMG tests, found that nickel release from earrings randomly purchased in China and Thailand was 31.5% and 29.2%, respectively. 11,13,16 The DMG test is used widely in clinical practice and by nickel-allergic individuals at home.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations